Reproduction of male reindeer (Rangifer tarandus) - Nagy, Sz.; Lindeberg, H.; Nikitkina, E.; Krutikova, A.; Smith, E.; Kumpula, J.; Holand, Ø. (Elsevier, 2021)
The present review provides a comprehensive assessment on the basic aspects of the reproduction of the Rangifer male with a special focus on pubertal development, and the seasonal dynamics of gametogenesis, androgenesis, antler cycle and other physiological and behavioural characteristics of the rutting male. A greater understanding of the reproductive physiology of the males is needed to improve existing management strategies of semi-domestic stocks in the changing climate and to develop species-specific assisted reproductive technologies for improving the in situ and ex situ conservation programs to preserve endangered subspecies as well as to facilitate the transfer of genetic resources between fragmented wild or semi-domestic populations.
Keywords: reindeer; reproduction; male; Gametogenesis; Androgenesis; male animals